Mata Rantai Perdagangan Lada di Kalimantan Bagian Tenggara Pada Abad ke-17-18 - Endang Susilowati (Department of History, Faculty of Humanities, Diponegoro University, 2020)
In the period of 17th century up to 18th century, pepper was one of the important commodities of Southeastern Kalimantan. Pepper was produced by Dayak tribes in rural areas of Southeastern Kalimantan, transported through the rivers and traded in Banjarmasin, which was the most important port in the region. Merchants from all around the globe visited Banjarmasin to trade for this commodity. This article aims to study the linkage of the pepper trade in Banjarmasin which involved pepper farmers in rural areas, Chinese and Banjar merchants as the middlemen, Sultan and court officials as the holders of privileges in pepper trade, and foreign traders (Chinese, Dutch, and the British) as the buyer of pepper in the port city of Banjarmasin. By discussing the role of each part of the link, the relationship between these parts can be seen clearly. The results of this study indicate that pepper farmers are the most disadvantaged party in this trade link, they hardly benefit from the growing trade of the pepper they produced. Meanwhile the middlemen, Sultan and court officials had enjoyed huge profits. The Sultan even used pepper as a political tool to gain the support of Dutch authorities (Dutch East-India Company) in dealing with their enemies. Another important link was the Chinese, Dutch and British merchants who competed for the pepper supplies. The Chinese traders who charged the pepper for a higher price had easier way to obtain the pepper supplies than the Dutch and British traders who were supported by their trading authorities.